Impact of organisation environment on control system and technological innovation for improving the firm performance of gold mining projects: case of Eastern African community - Sorasak Tangthong; Navidreza Ahadi (J for Global Business Advancement, 2022)
This research explores the link between the organisational environment, control system, and technological innovation, as well as their influence on corporate performance, using a structural equation model for gold mining enterprises in the Eastern African Community (EAC). Financial measurements including growth and profitability have been highlighted as important business concerns for gold-mining firms, and they are in the best interests of the company's stakeholders. Through technology improvements and control systems, the financial component has a substantial influence on managerial performance. A total of 390 gold mining executives from EAC enterprises participated in this survey. Six executives were chosen from each organisation. The results support the hypothesis by confirming positive relationships between research variables and theoretical framework alignment. Overall, an efficient control system, innovative technology, and a dynamic organisational environment are recommended for gold mining enterprises to improve their performance.
Keywords: Mining Techniques and Economics